Changes in Income Predict Change in Social Trust: A Longitudinal Analysis. Issue 6 (28th August 2014) - Brandt, Mark J.; Wetherell, Geoffrey; Henry, P. J.
Abstract : Social trust is a psychological variable important to politics, the community, and health. Theorists have predicted that socioeconomic status determines social trust, but also that social trust determines socioeconomic status. The current study tested the viability of both causal directions using longitudinal data from representative samples of the United States and the United Kingdom. Results demonstrated that a model where increases in socioeconomic status (measured by income) predict increases in social trust is more viable than a model where increases in social trust predict increases in socioeconomic status.